PELATIHAN PENULISAN CERITA ANAK BAGI MAHASISWA STIA-ASMI SOLO - Eka Susylowati; Widyashanti Kunthara Anindita; Ika Oktaria; Ani Susanti (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
This study aims to improve students' competence in writing children's stories. The research methods used lectures, observations, and discussions. The results showed that the level of competence in writing children's stories for STIA-ASMI students had progressed. Community service activities in the STIA-ASMI SOLO environment are very useful for STIA-ASMI SOLO students to improve their ability in writing children's stories